Integrity of Multiple Memory Systems in Individuals With Untreated Obstructive Sleep Apnea - Jackson, Melinda L.; Rayner, Genevieve; Wilson, Sarah; Schembri, Rachel; Sommers, Lucy; O’Donoghue, Fergal J.; Jackson, Graeme D.; Tailby, Chris (Frontiers in Neuroscience, 2020)
Obstructive sleep apnea (OSA) is associated with working- and autobiographical-memory impairments, and high rates of mood disorder. This study aimed to examine (i) behavioral responses and (ii) neural activation patterns elicited by autobiographical and working memory tasks in moderate-severe untreated OSA patients and healthy controls, and (iii) whether variability in autobiographical and working memory activation are associated with task performance, OSA severity and psychological symptomatology (depression, anxiety). In order to control for the potential confounding effect of elevated rates of clinical depression in OSA, we excluded individuals with a current psychiatric condition. Seventeen untreated OSA participants and 16 healthy controls were comparable with regards to both activation and behavioral performance. OSA was associated with worse subclinical mood symptoms and poorer personal semantic memory. Higher levels of nocturnal hypoxia were associated with increased activation in the occipital cortex and right cerebellum during the working memory task in OSA participants, however, no significant relationships between activation and task performance or depressive/anxiety symptomatology were observed. The neurocognitive substrates supporting autobiographical recall of recent events and working memory in younger, recently diagnosed individuals with OSA appear to be indistinguishable from healthy age-matched individuals. These findings point to the importance of early diagnosis and treatment of OSA in order to preserve cognitive function.